Basic biomechanics - Hall, Susan J. [ (Susan Jean)] , 1953- (McGraw-Hill, 2012)
This introduction to biomechanics uses the latest findings from the research literature to support and exemplify the concepts presented. Quantitative as well as qualitative examples of problems illustrate biomechanical principles